Mewasiatkan Organ Tubuh sebagai Objek Wasiat Berdasarkan Fiqih Kontemporer - Lubis, Syahddan Dintara (Lembaga Yasin AlSys, 2023)
This study discusses the review of juridical and Islamic law related to the field of medicine. There are several views of 'Fuqoha' scholars discussing the benefits of human organs as objects of wills based on contemporary fiqh. The research method used is normative juridical, which is a process to find a rule of law, legal principles and legal doctrines to answer the legal problems faced. The results show that selling human organs is not allowed, even in an emergency. However, scholars differ on the trade in human organs that are seen as